Death Note. Vol. 12, Finis - Oba, Tsugumi (Viz, 2007)
"The human whose name is written in this note shall die" ... Light Yagami, a straight-A high school student, picked up this "death note" dropped into the human world and used it to rid the world of criminals. Years have passed, and various forces have tried to gain possession of the note, but the battle stops here.